Americanist Culture History
XIII, 499 p.
Keywords: Americanist Culture History reprints thirty-nine classic works of Americanist archaeological literature published between 1907 and 1971. The articles, in which the key concepts and analytical techniques of culture history were first defined and discussed, are reprinted, with original pagination and references, to enhance the use of this collection as a research and teaching resource. The editors also include an introduction that summarizes the rise and fall of the culture history paradigm, making this volume an excellent introduction to the field's primary literature.